2014
DOI: 10.1016/j.orcp.2013.12.254
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours of overweight and obese women during pregnancy who achieve and exceed recommended gestational weight gain

Abstract: Summary Background Excessive gestational weight gain (GWG) is associated with increased risk of pregnancy-related complications, postpartum weight retention, and long-term obesity. Little is known about the behavioural habits of pregnant women who achieve and exceed recommended GWG. Method In 2011, qualitative interviews were conducted in Pennsylvania with post-partum women who were overweight or obese prior to pregnancy to ascertain their behaviours and attitudes regarding dietary habits, physical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
5
20
0
2
Order By: Relevance
“…However, a deeper examination revealed several narratives. In line with previous work [18, 27, 32, 33, 35, 37], women did not feel that their weight or indeed diet and exercise were priorities for midwives and other healthcare professionals. In the current study practitioners detached from the subject by employing terminology such as “BMI” and actions such as “keep an eye on [your weight].” Women also reported that there were not ready opportunities to ask questions about “nonroutine” or “nonemergency” topics.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, a deeper examination revealed several narratives. In line with previous work [18, 27, 32, 33, 35, 37], women did not feel that their weight or indeed diet and exercise were priorities for midwives and other healthcare professionals. In the current study practitioners detached from the subject by employing terminology such as “BMI” and actions such as “keep an eye on [your weight].” Women also reported that there were not ready opportunities to ask questions about “nonroutine” or “nonemergency” topics.…”
Section: Discussionsupporting
confidence: 75%
“…This phenomenon of self-monitoring has been reported elsewhere; for example, women who disengaged from an antenatal weight service cited confusion and disappointment about not being weighed regularly [34, 35] and reported self-monitoring in half of the sample of women which included those who exhibited both recommended and excess gestational weight gain. What is less clear are women's motivations for regular weighing.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, pregnant women are more likely to nominate barriers than enablers to changing behaviour, particularly diet changes which impacted others, such as family. Additionally, previous research has shown the ‘minor disorders of pregnancy’ such as food cravings, nausea and vomiting can be barriers to women making healthy dietary changes . Thirdly, research suggests that some women may view pregnancy as an opportunity to exercise less dietary restraint than other times in the life course .…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the same reluctance among clinicians to discuss the sensitive subject of weight may also apply to online contributors who may not want to offend their pregnant readers by discussing specific weight gain guidelines on their websites. This lack of information, from both clinicians and the Internet, may be compounded by misinformation, such as the widespread cultural belief of “eating for two,” that is often perpetuated and reinforced by pregnant women’s friends and family members [36-39]. …”
Section: Discussionmentioning
confidence: 99%